PENGARUH KECERDASAN EMOSIONAL, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA KOPERASI KARYAWAN PT. TELKOM SIPORENNU MAKASSAR - -, Sukmawati; Gani, Nurjaya (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The objectif of this research to examine the effect of emotional intelegence, job satisfaction, and the organizational commitment toward employees performance at Koperasi Telkom Siporennu Makassar. The research uses 35 respondent of 35 members of population. The data were analyzed by multiple regretion. The results stated tree independent variables there were positive and significantly influence toward employees performance, both simultaneously and partially. Key words: emotional intelegence, job satisfaction, organizational commitment, employees performance